Ways of Improving Deposit Policy of Commercial Banks (Texas Journal of Multidisciplinary Studies, 2024)
In the article, the deposit policy of commercial banks is considered the main part of the general banking policy, and defines the strategy and tactics of commercial banks' deposit activities. The strengthening of the requirements for macroprudential control implemented within the framework of the monetary policy of the Central Bank of the Republic of Uzbekistan causes problems such as the lack of long-term liquid resources in the national currency and the need for banks to achieve appropriate liquidity indicators. Therefore, our government is implementing a number of reasonable policies to develop and improve the deposit policy and financial stability of commercial banks. In addition, it is possible to study the availability of factors affecting the stability of the deposit base of commercial banks, the level of adequacy of the deposit base of commercial banks, the instability of interest rates set for savings and time deposits, and the effect of interest rates on the level of profitability